Additive manufacturing: exploring the social changes and impacts - Matos, F. (2019)
Despite the myriad of possibilities and applications of additive manufacturing (AM) technology, knowledge about the social impacts of this technology is very scarce and very limited in some areas. This paper explores how factors generated by the development of AM technology may create social impacts, affecting the health and social well-being of people, quality of life, working conditions, and the creation of wealth. This paper presents the results of an exploratory multiple case study conducted among four Portuguese organizations that use AM technology, aiming to determine their perceptions regarding the social impacts of AM, its effects, and causes. The results confirm that AM technology is mainly seen to create positive impacts on health and safety (regarding physical hazards), on expectations for the future, on leisure and recreation, on low disruption with the local economy, on economic prosperity, on the professional status, and on innovative employment types. Nevertheless, a negative impact was also found on health and safety (concerning hazardous substances), as well as several mixed and null impacts. The main limitations of the research arise from the use of a case study methodology, since the results can be influenced by contextual factors, such as the size of the organizations in the sample, and/or social, cultural, technological, political, economic, and ecological factors. This study gives an up-to-date contribution to the topic of AM social impacts and social changes, an area which is still little-explored in the literature.